Investigating the Contributing Factors to Teaching Anxiety during Teaching Practicum: A Case of Indonesian Pre-Service EFL Teachers - DINDA PERMATASARI; HERRI MULYONO; FERAWATI FERAWATI (Universitas Jambi, Indonesia, 2019)
A body of literature has shown that teaching anxiety is one among other critical issues encountered by pre-service teachers when performing classroom teaching during a teaching practicum program. The current study attempted to examine the contributing factors to this anxiety among pre-service teachers performed the teaching of English as a foreign language (EFL) during their practicum in primary and secondary schools in Indonesia. To this end, 202 pre-service EFL teachers were asked to complete Teaching Anxiety Scale (TCHAS) questionnaire. Statistical analyses were performed to the collected quantitative data. Findings of the study revealed that there was statistical difference between male and female on the anxiety factor of ‘being unable to answer students’ question’ (F = 6.724, p < .05) but not on other factors of ‘incompetent in classroom’ (F = 3.568, p>.05), ‘dislike teaching’ (F = .001, p>.05), ‘career uncertainty’ (F = 1.238, p>.05), and ‘the negative attitude of the students’ (F = 3.713, p>.05). Findings of the study also showed that teaching anxiety was experienced by pre-service EFL teachers teaching at primary school, lower secondary school and upper secondary school during the teaching practicum with similar level of anxiety.